Anomaly detection using clustering for ad hoc networks -behavioral approach- - Belacel Madani; B. Messabih (Computer Engineering and Applications Journal (ComEngApp), 2012)
Mobile   ad   hoc   networks   (MANETs)   are   multi-hop   wireless   networks   ofautonomous  mobile  nodes  without  any  fixed  infrastructure.  In  MANETs,  it  isdifficult to detect malicious nodes because the network topology constantly changesdue  to  node  mobility.  Intrusion  detection  is  the  means  to  identify  the  intrusivebehaviors and provide useful information to intruded systems to respond fast and toavoid  or  reduce  damages.  The  anomaly  detection  algorithms  have  the  advantagebecause  they  can  detect  new  types  of  attacks  (zero-day  attacks).In  this  paper,  wepresent  a  Intrusion  Detection  System  clustering-based  (ID-Cluster)  that  fits  therequirement of MANET. This dissertation addresses both routing layer misbehaviorsissues,  with  main  focuses  on  thwarting  routing  disruption  attack  Dynamic  SourceRouting  (DSR).  To  validate  the  research,  a  case  study  is  presented  using  thesimulation with GloMoSum at different mobility levels. Simulation results show thatour  proposed  system  can  achieve  desirable  performance  and  meet  the  securityrequirement of MANET.